Copper‐Promoted Direct Decarboxylative C3‐Acylation of Electron‐Rich Indolizines Using α‐Keto Acids. Issue 21 (1st June 2022) - Liu, Hao; Ren, Shaohong; Ma, Chuanjun; Shi, Guowei; Li, Yongchao; Duan, Guiyun; Ge, Yanqing
Abstract: C‐3 substituted indolizines are important biological heterocycles and luminescent molecules. The development of new methods for direct arylation of indolizines is highly desired. Herein, the C3‐acylation of electron‐rich indolizines with α‐keto acids through Cu‐promoted decarboxylation was descried. Under this simple reaction conditions, a variety of indolizine derivatives were synthesized and characterized. The structure of product 3 a was confirmed in an X‐ray crystal analysis. In addition, the mechanism was also proposed. Abstract : A simple methodology for the acylation of a variety of indolizines with α‐keto acids through Cu‐promoted decarboxylation was described. Under the optimized conditions, the desired products were obtained in moderate to good yields and were characterized by 1 HNMR, 13 C NMR and HRMS. The structure of product 3 a was further confirmed by X‐ray crystal analysis. In addition, the mechanism was also proposed.